Taḥlīlu Ḥarfi al Jarri fī alKitābi al Qirā’ati al Rasyīdati li Abī al Hasani ‘Alī al Husnī al Nadwī: Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Nahwi - Latifa, Intan Septia; Nurlaily, Nurlaily (Al-Uslub: Journal of Arabic Linguistic and Literature, 2023)
Learning jar letters analyzed in the Kitab Al-Qiroatir Rhosidah Li Abi Hasan An-Nadawi has various meanings of jar letters which are one of the problems in this study, while the objectives of this study are to: know the kinds of jar harfus, determine The word law which is located after Harfu Jar in the book of Al-Qiroatir Rhosidah Li Abi Hasan An-Nadawi. This type of research uses a literature study approach with jar letters as the object and analyzes using the book of nahwu rules. The source of the research data is the Kitab Al-Qiroatir Rhosidah Li Abi Hasan An-Nadawi. The object of this research is the number of harfu jars, determining the location of harfu jars, the meaning of harfu jars. The technique of this research is library research. The instrument used is the author assisted by text data, writing instruments and a laptop. And the method used to analyze the data is a description of the analysis. The results of this study the authors conclude that: as for the number of jar harfu there are 295 words. the letter min has 50 words and has 5 meanings, and the letter ila has 48 words and has 3 meanings, and the letter an has 10 words and has 3 meanings, and the letter ala has 20 words and has 6 meanings, and the letter fi has 112 words and has 5 meanings, and the letter ba has 38 ka and has 5 meanings, and the lam letter has 17 words and has 6 meanings, and the last letter kaf has 1 word, namely the meaning of attaukid.